Angiogenesis and anti-leukaemia activity of novel indole derivatives as potent colchicine binding site inhibitors - Yongfang Yao; Tao Huang; Yuyang Wang; Longfei Wang; Siqi Feng; Weyland Cheng; Longhua Yang; Yongtao Duan (Taylor & Francis Group, 2022)
The screened compound DYT-1 from our in-house library was taken as a lead (inhibiting tubulin polymerisation: IC50=25.6 µM, anti-angiogenesis in Zebrafish: IC50=38.4 µM, anti-proliferation against K562 and Jurkat: IC50=6.2 and 7.9 µM, respectively). Further investigation of medicinal chemistry conditions yielded compound 29e (inhibiting tubulin polymerisation: IC50=4.8 µM and anti-angiogenesis in Zebrafish: IC50=3.6 µM) based on tubulin and zebrafish assays, which displayed noteworthily nanomolar potency against a variety of leukaemia cell lines (IC50= 0.09-1.22 µM), especially K562 cells where apoptosis was induced. Molecular docking, molecular dynamics (MD) simulation, radioligand binding assay and cellular microtubule networks disruption results showed that 29e stably binds to the tubulin colchicine site. 29e significantly inhibited HUVEC tube formation, migration and invasion in vitro. Anti-angiogenesis in vivo was confirmed by zebrafish xenograft. 29e also prominently blocked K562 cell proliferation and metastasis in blood vessels and surrounding tissues of the zebrafish xenograft model. Together with promising physicochemical property and metabolic stability, 29e could be considered an effective anti-angiogenesis and -leukaemia drug candidate that binds to the tubulin colchicine site.